2020
DOI: 10.1111/mec.15409
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of an evolutionary innovation: Gene expression differences associated with the transition between oviparity and viviparity

Abstract: Our understanding of the evolution of complex biological traits is greatly advanced by examining taxa with intermediate phenotypes. The transition from oviparity (egg‐laying) to viviparity (live‐bearing) has occurred independently in many animal lineages, but there are few phenotypic intermediates. The lizard Saiphos equalis exhibits bimodal reproduction, with some viviparous populations, and other oviparous populations with long egg‐retention, a rare trait where most of embryonic development occurs inside the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 75 publications
1
32
0
Order By: Relevance
“…Although not directly measured, it is inferred that viviparous species with placentation exchange respiratory gases and this is facilitated by changes in maternal blood chemistry that enhances oxygen exchange (Ingerman et al, 1991). To fully understand the link between oxygen demand, oxygen transport and reproductive mode, examples of within‐species (Rechnagel et al, 2021) and within‐individual variation (Laird et al, 2019), that is, showing both oviparous and viviparous reproductive modes, as well as cross‐species comparisons (Foster et al, 2020) all provide ideal opportunities to link evolutionary form to function. Our analysis suggests that changing blood oxygen‐carrying capacity by altering size and/or shape of erythrocytes is one mechanism to avoid constraints of low oxygen and may allow viviparous Lepidosauria to exploit higher altitude areas.…”
Section: Discussionmentioning
confidence: 99%
“…Although not directly measured, it is inferred that viviparous species with placentation exchange respiratory gases and this is facilitated by changes in maternal blood chemistry that enhances oxygen exchange (Ingerman et al, 1991). To fully understand the link between oxygen demand, oxygen transport and reproductive mode, examples of within‐species (Rechnagel et al, 2021) and within‐individual variation (Laird et al, 2019), that is, showing both oviparous and viviparous reproductive modes, as well as cross‐species comparisons (Foster et al, 2020) all provide ideal opportunities to link evolutionary form to function. Our analysis suggests that changing blood oxygen‐carrying capacity by altering size and/or shape of erythrocytes is one mechanism to avoid constraints of low oxygen and may allow viviparous Lepidosauria to exploit higher altitude areas.…”
Section: Discussionmentioning
confidence: 99%
“…In Australian lizards, evidence of obligate placentotrophy of organic nutrients is so far limited to skinks in the genera Carinascincus and Pseudemoia; candidate nutrient transporters in these taxa include lipoprotein lipase, and amino acidtransporting solute carriers (SLCs: Griffith et al 2013Griffith et al , 2016. Gene expression analyses, particularly transcriptomic studies, have identified thousands of genes that are likely to be involved in pregnancy in Australian lizards (Griffith et al 2016Hendrawan et al 2017;Foster et al 2020). These genes likely contribute to key pregnancy-related functions including uterine remodelling, nutrient and respiratory gas transport, and immune regulation, and testing the functions of these genes is the next step in understanding their role in the evolution of viviparity.…”
Section: Viviparity and Placentationmentioning
confidence: 99%
“…The evolution of this type of reproductive complexity is currently of broad interest to evolutionary biologists (e.g. Van Dyke et al ., ; Griffith et al ., ; Pyron, ; Blackburn, ; Whittington et al ., ; Buddle et al ., ; Cornetti et al ., ; Gao et al ., ; Foster et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Studies in a variety of vertebrates show that viviparous and oviparous parents exhibit differences in endocrine activity and metabolism, tissue remodelling and vascularity, nutrient provisioning, immune function, behaviour and performance, and regulation of gene expression (e.g. Qualls & Shine, ; Heulin et al ., , ; Adams et al ., ; Murphy & Thompson, ; Callard et al ., ; Whittington et al ., ; Griffith et al ., ; Foster et al ., ). These differences make parity mode a compelling subject for studies of comparative physiology, evolutionary biology, and the genetic basis of novel phenotypes.…”
Section: Introductionmentioning
confidence: 97%